Drunk or disordered: a TUC guide to tackling alcohol and drugs at work (London, 2001)
"Drink and drug related problems are one of the commonest causes of sickness absence, yet a large number of organisations do not have a drug and alcohol policy. Substance misusers jeopardize their own health and can affect the safety of colleagues. This guide shows how proper policies to deal with the effects of substance misuse, and constructive procedures for supporting victims, can achieve far more than testing programmes alone."